2009
DOI: 10.1007/s00464-009-0672-3
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide synthase inhibition aggravates the adverse renal effects of high but not low intraabdominal pressure

Abstract: Decreased renal function/perfusion is induced by IAP pressures of 10 and 14 mmHg but not 7 mmHg. Inhibition of NOS aggravates the adverse renal effects of high (14 mmHg) but not low (7 or 10 mmHg) IAP, indicating that NO deficiency may contribute to the renal dysfunction during high IAP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 43 publications
0
5
0
1
Order By: Relevance
“…A previous study revealed that the glomerular filtration rate decreased by 14 and 48% in rats when an intraabdominal pressure of 7 and 14 mmHg was applied, respectively. In parallel, the renal plasma flow decreased by 28 and 57% under these conditions ( 29 ). Certain studies have emphasized that high intraabdominal pressure can noticeably decrease renal blood flow, while other studies reported that renal blood flow returned to the normal range following deflation ( 30 , 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study revealed that the glomerular filtration rate decreased by 14 and 48% in rats when an intraabdominal pressure of 7 and 14 mmHg was applied, respectively. In parallel, the renal plasma flow decreased by 28 and 57% under these conditions ( 29 ). Certain studies have emphasized that high intraabdominal pressure can noticeably decrease renal blood flow, while other studies reported that renal blood flow returned to the normal range following deflation ( 30 , 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…Essentially, blockade of NOS with L-NAME was found to aggravate pneumoperitoneum-induced renal hypoperfusion and oliguria, while pretreatment with nitroglycerine attenuated this effect. 2 9 Bishara, et al 18 reported the importance of IAP by showing that blockade of the NO system with L-NAME had adverse renal effects at high yet not moderate IAPs. Moreover, they found in another study that rats with decompensated congestive heart failure were more susceptible to the adverse renal effects of pneumoperitoneum when pretreated with L-NAME, implying a higher susceptibility to kidney function deterioration in patients with cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 99%
“… 22 Moreover, the functional significance of arginase and its relevance with the activity of NOS was emphasized due to the fact that arginase and NOS share L-arginine as a substrate. 11 However, while oxidative stress, tissue injury, and reduction in kidney function during laparoscopic surgery have been suggested to be closely related to the NO system in several recent studies, 1 9 18 the role of arginase during CO 2 pneumoperitoneum has remained unknown. Considering the fact that competition for L-arginine supply is intensified under acute and chronic stress conditions, 23 arginase may contribute to the shortage of NO bioactivity during laparoscopic surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In rat studies, the administration of nitric oxide alleviates the renal effect of pneumo-peritoneum at a higher (14 mmHg compared to 7 and 10 mmHg) pressure by about 40%, as can be gleaned from a bar chart in Bishara et al, while the nitric oxide synthase inhibitor aggravates it by approximately 50% [ 117 , 118 ].…”
Section: Humoral Factorsmentioning
confidence: 99%